Comparison of ESG Rating Methods with AHP Methods (A Study in A State-Owned Electricity Company in Indonesia) - Jonatan Halomoan; Dewi Hanggraeni (Quantitative Economics and Management Studies, 2024)
The ESG Rating measurement method from Sustainalytic & S&P is the method that is considered the most suitable for analyzing ESG risks in State-owned electricity companies. This research analyzes the ESG Rating measurement method issued by 4 ESG rating agencies, namely S&P, MSCI, Sustainalytics, and Refinitiv using the method AHP, the results of which will determine which method is most suitable for analyzing ESG risks in state-owned electricity companies. From the results of data collection, it was found that the ESG rating measurement method from Sustainalytic had the highest priority value, namely 38.9%, which was not much different from the method from S&P with a value of 34.0%. Meanwhile, the methods of the other 2 ESG rating agencies have a lower weight, namely MSCI with 14.2% and Refinitiv with 12.9%. Research provides the view that the level of correlation between rating agencies is still low, requiring companies to first analyze the rating agency. The ones they choose will determine the company's strategy in managing their ESG risks.